INVIGORATING WORLD SYSTEM THEORY as CRITICAL THEORY: Exploring Philosophical Foundations and Postpositivist Contributions - Kurt Burch (Journal of World-Systems Research, 1995)
World system theory comprises two distinct lines of inquiry: macro-social studies of historical world-systems and ideological critique. World system theorists often shun ideological critique, but for two reasons I argue it must be foremost. First, without explicit attention to its philosophical foundations, world system theory rests upon several unexamined, uncomplementary, liberal premises. These premises pose conceptual puzzles. World system theorists frequently cast such puzzles as methodological, empirical, or theoretical problems, rather than as symptoms of ideological confusions requiring critique. Second, through explicit critique, theorists may transform implicit philosophical foundations into explicit ontological and epistemological groundings. Such groundings will enable world system theorists to better realize their critical, emancipatory goals and to resolve theoretical puzzles. One such puzzle -- the conceptual distinction between politics and economics -- recurs often, arising in the debates on the relation(s) between the state system and capitalism and thwarting efforts to demonstrate the unity of the world system. I suggest that world system theorists engage in explicit ideological critique to lay equally explicit ideologicalfoundations for their histories. I suggest a critical, conceptually historicist, "constructivist" approach that builds upon postpositivist critiques and introduces constitutive principles. I illustrate the virtue of this approach by demonstrating the unity of the modern world system.